Generation of auxin inducible degron (AID) knock-in cell lines for targeted protein degradation in mammalian cells - Bikash Adhikari (Elsevier, 2021)
Summary: Targeted protein degradation using degrons, such as the mini-Auxin-inducible degron (mAID), has an advantage over genetic silencing/knockout. However, the efficiency of sgRNA, homologous recombination, tedious expansion, and screening single clones makes the process of tagging endogenous proteins long and laborious. This protocol describes a practical and economical way to obtain AID-tagged endogenous proteins using CRISPR/Cas9-mediated homology-directed repair (HDR). We use the generation of endogenously AID-tagged SPT6 in U2OS cells as an example but provide sufficient details for usage in other cell types.For complete details on the use and execution of this protocol, please refer to Narain et al. (2021).